Structural and magnetic properties of topotactically reduced YSr2Mn2O7-x (0 < x < 1.5) - Hayward, M (2006)
Reaction of the n = 2 Ruddlesden-Popper phase YSr2Mn 2O7 with NaH at 225 °C yields the topotactically reduced phase YS2Mn2O5.43(3) (a = 3.62043(4) Å, c = 22.3570(3) A). Combination of this reduced phase with the stoichiometric starting material at 400 °C yields intermediate phases: YSr2-Mn2O6.54(3) (a = 3.80900(7) Å, c = 20.2691(5) Å) and YSr2Mn2O5.96(3) (a = 3.81071(7) Å, c = 20.5238-(4) Å). The variation in the anion vacancy distribution of these reduced phases as a function of stoichiometry is discussed in relation to the coordination polyhedra of the metal cations. Temperature-dependent magnetization data indicate strong antiferromagnetic coupling interactions in all samples. Long-range magnetic order is suppressed by structural or charge disorder in all samples except YSr2Mn 2O5.5, which adopts a G-type antiferromagnetic ordering scheme with an ordered moment of 4.61(5)μB per manganese, consistent with S = 5/2 Mn(II). © 2006 American Chemical Society.